A screening gate to prevent entry of mobile telephone handsets in the speaking - Hanada, E. (IEEE Transactions on information technology in biomedicine)
Electromagnetic interference to electronic equipment by mobile telephone handsets is well known. We present an automatic screening gate that detects concealed mobile telephone handsets and classifies them by type. The screening method used in the gate does not require any additions to or reconstruction of mobile telephone systems.